PENGARUH DIGITAL LITERACY TERHADAP EMPLOYABILITY DI RUMAH SAKIT TIPE B DI PROVINSI BANTEN - Kristie, Karina; Kornarius, Yoke Pribadi; Caroline, Angela; Gunawan, Agus (Bajang Institute, 2025)
This study aims to evaluate the impact of digital literacy on the employability of healthcare professionals in type B hospitals in Banten Province. Digital literacy is defined as the ability to search, comprehend, and effectively utilize digital information, which has become increasingly important in the era of digital transformation. Employability refers to an individual's ability to secure and retain employment by leveraging their skills and knowledge. This quantitative study employed a descriptive analysis method involving 132 respondents from healthcare professionals with undergraduate and diploma degrees. The results revealed that digital literacy influences employability by 41.5%, while the remaining 58.5% is influenced by other factors. Respondents with undergraduate degrees tend to have higher digital literacy and employability levels than those with diplomas. This highlights the importance of integrating digital literacy into healthcare education curricula and providing additional training to improve these skills in the workplace. This study offers strategic insights for hospitals and educational institutions to prepare healthcare professionals for future digital challenges.